Prediction of ZnO Surge Arrester Degradation Based on Temperature and Leakage Current Properties - Novizon Novizon; Zulkarnain Abdul-Malek; Aulia Aulia; Eka Putra Waldi; Abdul Rajab; Darwison Darwison (Jurusan Teknik Elektro Universitas Andalas, 2018)
Temperature and leakage current on the ZnO arrester are interrelated with each other. In low conduction region, voltage-current characteristics of ZnO surge arrester are highly dependent on temperature. The leakage current will increase as the temperature increases and experience thermal runaway when the temperature exceeds the acceptable limit. This phenomenon is associated with the increase of resistive leakage current due to degradation. Therefore the temperature and leakage current are good indicator to evaluate the condition of ZnO arrester. This paper proposed the degradation prediction of ZnO surge arrester by analyzed the temperature and leakage current. The 132 kV station type ZnO surge arrester was employed. Temperature profile of ZnO arrester was obtained using thermal camera. The leakage current was measured simultaneous with the temperature measurement to attain the leakage current at the actual temperature. The results shows the leakage current continue increasing by increasing the temperature. Keywords : Resistive leakage current, temperature, degradation, prediction, zinc oxide surge arrester